PHYSIOLOGICAL EFFECTS OF LEAD ,CADMIUM AND THEIR MIXTURE ON SOME ORGANS OF Alburnus Mossulensis FISH - R .S. Al-Niemi,; Amal A. Al-Kshab, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Alburnus mossulensis has been exposed to lead and cadmium for (96)h in order to determination lethal concentration 50 (LC50) value. A total of 140 fish used in this experiment divided into two groups each group contain 70 fishes .The first group exposure to pbcl2 while the second group exposure to cdcl2. Method of Finney Probit Analysis used to analysis data. LC50  value for PbCl2 and CdCl2 was (57.8 and 29.6) mg/l respectively. Then used about 200  fishes divided into 4 groups, the first group exposure to 1/2LC50  of PbCl2 ,the second group exposure to 1/2LC50 CdCl2 while the third groups contained (1/2LC50 PbCl2+1/2LC50 of CdCl2) as so as control group for peroids (1,4,7 and 14) days to determination level of antioxidants Glutathione (GSH) and the level of lipid peroxidation (Malondialdehyde MDA) . The testes were carried out as three replications, lead ,cadmium and their mixture induced  oxidative stress . The results of this study  explained significant decrease of the level Glutathione and significant increase (Tukey test, P˂0.05)  of the level of Malondialdehye compared with control in all treatments .  It is possible to conclude that lead and Cadmium have cytotoxic effects, Fish mortality rates increase with increasing concentrations used and increasing exposure periods.